Corporate Social Responsibility, Firm Size, Inflation, Interest Rate, and Exchange Rate on Stock Returns - Yunita Rochmayasari (Publindo Akademika, 2022)
This study aims to examine the effect of partially and simultaneously between corporate social responsibility, firm size, inflation, interest rates, and exchange rates on stock returns. This research uses quantitative methods. The population in this study are all automotive and their components sub-sector companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sample selection technique uses a purposive sampling method. The sample in this study was six automotive companies, and their components used quarterly data, so a total of 120 samples. The analysis technique used is multiple linear regression analysis with the help of SPSS software version 20. The partial analysis results show that corporate social responsibility and interest rates have a negative and not significant effect on stock returns. Firm size, inflation and exchange rates have a positive and not significant effect on stock returns. Simultaneously corporate social responsibility, firm size, inflation, interest rates, and exchange rates do not affect stock returns.